Neuromuscular and Perceptual Responses to Sub-Maximal Eccentric Cycling - Clos, Pierre; Laroche, Davy; Stapley, Paul J.; Lepers, Romuald (Frontiers in Physiology, 2019)
Objective: Eccentric (ECC) cycle-ergometers have recently become commercially-available, offering a novel method for rehabilitation training. Many studies have reported that ECC cycling enables the development of higher levels of muscular force at lower cardiorespiratory and metabolic loads, leading to greater force enhancements after a training period. However, fewer studies have focused on the specific perceptual and neuromuscular changes. As the two latter aspects are of major interest in clinical settings, this review aimed to present an overview of the current literature centred on the neuromuscular and perceptual responses to submaximal ECC cycling in comparison to concentric (CON) cycling. Design: Narrative review of the literature. Results: At a given mechanical workload, muscle activation is lower in ECC than in CON while the characteristics of the musculo-articular system (i.e., muscle-tendon unit, fascicle, and tendinous tissue length) are quite similar. At a given heart rate or oxygen consumption, ECC cycling training results in greater muscular hypertrophy and strength gains than CON cycling. On the contrary, CON cycling training seems to enhance more markers of muscle aerobic metabolism than ECC cycling performed at the same heart rate intensity. Data concerning perceptual responses, and neuromuscular mechanisms leading to a lower muscle activation (i.e., neural commands from cortex to muscular system) at a given mechanical workload are scarce. Conclusion: Even though ECC cycling appears to be a very useful tool for rehabilitation purposes the perceptual and neural commands from cortex to muscular system during exercise need to be further studied.